Biology and Management of Exploited Crab Populations Under Climate Change 2011
DOI: 10.4027/bmecpcc.2010.24
|View full text |Cite
|
Sign up to set email alerts
|

Podding Behavior of Adult King Crab and Its Effect on Abundance-Estimate Precision

Abstract: The Alaska red king crab, Paralithodes camtschaticus, is a major target of the Bristol Bay stock assessment bottom-trawl survey conducted annually by the U.S. National Marine Fisheries Service. Because of the difficulty of sampling extremely patchy spatial distributions, it is important to know whether the podding behavior documented for juvenile red king crab continues into adulthood. A common assumption is that adults are not podding crab. I present data from in situ investigations at Kodiak and adaptive clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Aggregations of small crabs, presumably small individuals of grooved tanner crab, were observed in several occasions on small elevations of the seabed or on a short hydrate mound (Supplementary Figure 3; Supplementary Video 11). Further studies are needed to understand this behavior, with small decapods previously observed climbing on seabed structures to escape the anoxic first few cm of the BBL (Doya et al, 2016), and generally aggregating as a defense mechanism (Dew, 2010). Doya et al (2017) reported an agonistic interaction between a grooved tanner crab and a scarlet king crab over a piece of food.…”
Section: Crabsmentioning
confidence: 99%
“…Aggregations of small crabs, presumably small individuals of grooved tanner crab, were observed in several occasions on small elevations of the seabed or on a short hydrate mound (Supplementary Figure 3; Supplementary Video 11). Further studies are needed to understand this behavior, with small decapods previously observed climbing on seabed structures to escape the anoxic first few cm of the BBL (Doya et al, 2016), and generally aggregating as a defense mechanism (Dew, 2010). Doya et al (2017) reported an agonistic interaction between a grooved tanner crab and a scarlet king crab over a piece of food.…”
Section: Crabsmentioning
confidence: 99%
“…Podding refers to structurally dense and socially organized groups of organisms in aggregations. In these pods, all individuals are similar in size and are in physical contact with one another (Stone et al, 1993;Dew, 2010). Our observations are the first report of podding in the Chilean false king crab in sub-Antarctic kelp forests.…”
Section: Resultsmentioning
confidence: 52%
“…Podding behavior is probably a generalized characteristic of lithodids such as in Paralithodes J.F. Brandt, 1848 (Loher and Armstrong, 2000;Dew, 2010) and L. santolla (see Cárdenas et al, 2007). This behavior has been well documented for other crustaceans of the family Majidae, including Chionoecetes bairdi Rathbun, 1924 (Stevens et al 1994;Zhou and Shirley, 1997), Chionoecetes opilio O. Fabricius, 1788 (Comeau et al, 1998), Hyas lyratus Dana, 1851 (Stevens et al, 1992), and Maja squinado (Herbst, 1788) (Sampedro and González-Gurriarán, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…The 2.5-month lag correlation between cohort 1-3 (<1.9 cm) and cohort 4 (2-2.8 cm) could reflect the time lag between two molts, as observed between November 2012 and February 2013. The major aggregations observed in February are likely a result of gathering behavior for molting (e.g., Dew, 2010). Based on our correlation results, an additional 13.5 months were required to grow from cohort 4 to cohort 7 (from 3 cm to >5 cm).…”
Section: Discussionmentioning
confidence: 85%